Age, Digital Financial Literacy and Saving Behavior among Households in West Bandung: A Microdata Study - Siagian, Valentine; Pakpahan, Andrew Fernando; Sinaga, Judith Tagal Gallena (12th International Scholars Conference 2025, 2026)
This study examines the influence of age and digital financial literacy on saving behavior among households in West Bandung, Indonesia. As financial technology becomes increasingly integrated into everyday life, understanding how different age groups engage with digital financial tools is essential for promoting inclusive financial practices. The study aims to explore the direct and indirect effects of age on saving behavior, with digital financial literacy as a potential mediating factor. Data were collected through a structured questionnaire distributed during a women’s ministry meeting, targeting female household representatives. Respondents could choose between an online Google Form or paper-based format, accommodating a wide age range. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the data and test the proposed relationships. Results show that digital financial literacy has a strong positive effect on saving behavior (β = 0.629), while age has a positive direct effect on saving behavior (β = 0.274) and a marginal negative effect on digital financial literacy (β = -0.197). The model explains 40.2% of the variance in saving behavior, suggesting a meaningful interaction between age, financial knowledge, and saving practices. The findings highlight the dual role of age: as a contributor to disciplined saving and as a barrier to digital tool adoption. This underscores the need for age-sensitive financial literacy programs that enhance digital confidence without neglecting traditional saving values. The study offers valuable insights for policymakers and practitioners seeking to improve financial inclusion in semi-urban communities.